Analisis Tingkat Kepuasan Pengguna Layanan Jaringan Indihome Menggunakan Metode Importance Performance Analisysis (IPA) - Angela Putri Larasati Darakay; Magdalena A. Ineke Pakereng (JURIKOM (Jurnal Riset Komputer), 2022)
User satisfaction with the services provided has a very important meaning for a company or service provider that aims to benefit the company or service provider itself. The research was conducted on the Analysis of the Satisfaction Level of Indihome Service Use (Wifi) using the Importance Performance Analysis (IPA) method. In the modern era, the internet is growing rapidly from time to time which has resulted in more and more internet service providers. This is the reason for internet service providers to pay attention to the level of service quality and the level of customer satisfaction. The results showed that the level of suitability for Indihome services ranged from 77% - 107%, which means that the performance provided to customers is quite good.